Antimicrobial Effects of Selected, Cultivated Red Seaweeds and Their Components in Combination with Tetracycline, against Poultry Pathogen Salmonella Enteritidis - Garima Kulshreshtha; Alan Critchley; Bruce Rathgeber; Glenn Stratton; Arjun H. Banskota; Jeff Hafting; Balakrishnan Prithiviraj (Journal of Marine Science and Engineering, 2020)
Poultry and its products are an economical source of high-quality protein for human consumption. In animal agriculture, antibiotics are used as therapeutic agents to treat disease in livestock, or as prophylactics to prevent disease and in so doing enhance production. However, the extensive use of antibiotics in livestock husbandry has come at the cost of increasingly drug-resistant bacterial pathogens. This highlights an urgent need to find effective alternatives to be used to treat infections, particularly in poultry and especially caused by drug-resistant Salmonella strains. In this study, we describe the combined effect of extracts of the red seaweeds Chondrus crispus (CC) and Sarcodiotheca gaudichaudii (SG) and compounds isolated from these in combinations with industry standard antibiotics (i.e., tetracycline and streptomycin) against Salmonella Enteritidis. Streptomycin exhibited the higher antimicrobial activity against S. Enteritidis, as compared to tetracycline with a MIC25 and MIC50 of 1.00 and 1.63 μg/mL, respectively. The addition of a water extract of CC at a concentration of 200 µg/mL in addition to tetracycline significantly enhanced the antibacterial activity (log CFU/mL 4.7 and 4.5 at MIC25 and MIC50, respectively). SG water extract, at 400 and 800 µg/mL (p = 0.05, n = 9), also in combination with tetracycline, showed complete inhibition of bacterial growth. Combinations of floridoside (a purified red seaweed component) and tetracycline (MIC25 and MIC50) in vitro revealed that only the lower concentration (i.e., 15 μg/mL) of floridoside potentiated the activity of tetracycline. Sub-lethal concentrations of tetracycline (MIC50 and MIC25), in combination with floridoside, exhibited antimicrobial activities that were comparable to full-strength tetracycline (23 μg/mL). Furthermore, the relative transcript levels of efflux-related genes of S. Enteritidis, namely marA, arcB and ramA, were significantly repressed by the combined treatment of floridoside and tetracycline, as compared to control MIC treatments (MIC25 and MIC50). Taken together, these findings demonstrated that the red seaweeds CC and SG and their selected, purified components can be used to increase the lifetime of existing, patented antibiotics and can also help to reduce costly (economic and environmental) therapeutic and prophylactic use of antibiotics in poultry. To our knowledge, this is the first report of antibiotic potentiation of existing industry standard antibiotics using red seaweeds and their selected extracts against S. Enteritidis.